Analysis of engaged online collaborative discourse: a methodological approach - Malheiro, Sofia (2018)
The purpose of this chapter is to present a reflection on collaborative learning mediated by the computer, discussing some difficulties and methodological constraints that we encounter when we try to analyze the interactions that occurred in this collaboration in an online course and the level of involvement in ollaborative discourse produced by participants. For we apply the Speech Involvement Scale Collaborative Computer-mediated Conference.